Observing the impact of profession change on 'habits of mind': A factor oriented approach. Issue 2 (November 2022) - Negi, Tanuj; Jain, Shashi
A common observation in Transformative Learning (TL) literature is the scarcity of ways to gauge the extent of personal transformation. This is despite a recorded history of more than four decades and the existence of multiple schools of thought in TL. Also, there has been insufficient exploration of the personal transformation of profession changers in the TL space. We believe it is important to operationalize the key concepts of the TL theory through quantitative methods to make way for newer insights. In this paper, using the case of profession changers from India, we extend Mezirow's work on six types of 'Habits of Mind' beyond their original conceptualization by identifying constituent latent factors. We examine and establish the reliability and validity of these factors and recommend a factor-based scale approach for application.